Bacillus cereus Improves Performance of Brazilian Green Dwarf Coconut Palms Seedlings With Reduced Chemical Fertilization - Cardoso, Aline Figueiredo; Alves, Ediane Conceição; da Costa, Sidney D. Araújo; de Moraes, Alessandra Jackeline Guedes; da Silva Júnior, Dalton Dias; Lins, Paulo Manoel Pontes; da Silva, Gisele Barata (Frontiers in Plant Science, 2021)
Coconut production in the Amazon requires the knowledge and development of sustainable technologies to alleviate the detrimental effects of inorganic chemical fertilizers and intensive farming practices. In this study, we investigated the effects of plant growth-promoting rhizobacteria (PGPR) isolated from coconut seedlings on nutrient use efficiency (NUE) and physiological mechanisms related to biomass accumulation of seedlings grown with reduced inorganic fertilizer levels. Of the 96 PGPR isolates tested on rice plants, the isolate Bacillus cereus (UFRABC40) was selected, as it resulted in the most significant gain in growth variables. In a commercial coconut tree nursery, we subjected seedlings to two treatments, both with seven replications: control 100% NPK chemical fertilizer (CF) and B. cereus + 50% NPK CF. The results indicated that the inoculation increased phytohormone levels (190% indole acetic acid (IAA), 31% gibberellic acid GA3 and 17% gibberellic acid GA4) and leaf gas exchange (48% by assimilation of CO2 (A), 35% stomatal conductance to water vapor (gs), 33% transpiration and 57% instantaneous carboxylation efficiency) in leaves. Furthermore, growth parameters (shoot, root, and total dry weight, height, and diameter) and macro and micronutrient levels (95% N, 44% P, 92% K, 103 Ca, 46% Fe, 84% B) were improved. Our results show the potential ability of strain Bacillus cereus UFRABC40 to promote the growth performance of coconut seedlings under decreased application of inorganic fertilizers. The application of microbial based products in coconut seedling production systems improves plants physiological performance and the efficiency of nutrient use.